Intergroup ‘Skype’ Quiz Sessions in Care Homes to Reduce Loneliness and Social Isolation in Older People - Sonam Zamir; Catherine Hennessy; Adrian Taylor; Ray Jones (Geriatrics, 2020)
Video calls using software such as Skype, Zoom and FaceTime can improve socialisation among older people and family, however it is unknown if video calls are able to improve socialisation among older people and their peers. Twenty-two residents across three British care homes engaged with each other using ‘Skype quiz’ sessions with the support of staff once a month over an eight-month trial. Video calls were accessed via a ‘Skype on Wheels’ intervention that comprised a wheeled device that could hold an iPad, or through Skype TV. Residents met other residents from the three care homes to build new friendships and participate in a thirty-minute quiz session facilitated by eight staff. Staff were collaborators who recruited older people, implemented the intervention and provided feedback that was analysed using thematic analysis. Residents enjoyed being able to see other residents’ faces and surroundings. Analysis of the field notes revealed five themes of: residents with dementia remember faces not technology, inter and intra connectedness, re-gaining sense of self and purpose, situational loneliness overcome and organisational issues create barriers to long-term implementation. Inter-care home connection through video calls to reduce feelings of loneliness in residents seems acceptable and a feasible, low cost model, especially during times of public crisis such as COVID-19.